WEB-BASED MAIL DATA MANAGEMENT INFORMATION SYSTEM IN THE DEPARTMENT OF CAPITAL INVESTMENT AND ONE-Stop INTEGRATED SERVICES WEST SUMATRA PROVINCE - Rijal, Muhammad (Universitas PGRI Sumatera Barat, 2024)
This research intends to create a web-based mail data management information system at Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Provinsi Sumatera Barat which can facilitate archivists in managing correspondence so as to speed up correspondence processing, make it easier for archivists to find evidence of correspondence, can store, change, print correspondence data and reduce the accumulation of archives in the workspace in the Secretariat. This research method is carried out by collecting data through internships, observations and interviews. The method used in developing this system uses the SDLC concept. At the analysis stage, the system modeling uses the Unified Modeling Language (UML) as a design tool. The implementation process is carried out using the MySQL database and the PHP programming language. The process of testing this system is carried out using the Black Box testing method. The results of the trial of the designed system have been in accordance with the needs expected by the agency. This research has produced a mail data management information system at Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Provinsi Sumatera Barat